Letter knowledge in parent–child conversations: differences between families differing in socio-economic status - Robins, Sarah; Ghosh, Dina; Rosales, Nicole; Treiman, Rebecca (Frontiers in Psychology, 2014)
When formal literacy instruction begins, around the age of 5 or 6, children from families low in socioeconomic status (SES) tend to be less prepared than children from families of higher SES. The goal of our study is to explore one route through which SES may influence children’s early literacy skills: informal conversations about letters. The study builds on previous studies (Robins, Treiman, & Rosales, 2014; Robins, Treiman, Rosales, & Otake, 2012; Robins & Treiman, 2009) that show how U. S. parents and their young children talk about writing and provides preliminary evidence about similarities and differences in parent–child conversations as a function of SES. Focusing on parents and children aged three to five, we conducted five separate analyses of these conversations, asking whether and how family SES influences the previously established patterns. Although we found talk about letters in both upper and lower SES families, there were differences in the nature of these conversations. The proportion of letter talk utterances that were questions was lower in lower SES families and, of all the letter names that lower SES families talked about, more of them were uttered in isolation rather than in sequences. Lower SES families were especially likely to associate letters with the child’s name, and they placed more emphasis on sequences in alphabetic order. We found no SES differences in the factors that influenced use of particular letter names (monograms), but there were SES differences in two-letter sequences (digrams). Focusing on the alphabet and on associations between the child’s name and the letters within it may help to interest the child in literacy activities, but they many not be very informative about the relationship between letters and words in general. Understanding the patterns in parent–child conversations about letters is an important first step for exploring their contribution to children’s early literacy skills and school readiness.